ON THEORY OF REMEDIAL SECESSION IN CONTEMPORARY INTERNATIONAL LAW - S. R. Aleksanian (Московский журнал международного права, 2018)
Introduction. Secession as a way of realization of the right of peoples to self-determination is disputed in contemporary international law, which distinguishes several secession theories. Of particular interest is the theory of remedial secession, which is based on the right to secede from a state under certain circumstances. It is argued that application of the theory of remedial secession is justified in cases of systematic, gross and massive violations of human rights, which endangers the existence of a national minority or a people, as well as when the policy of genocide, apartheid or ethnic cleansing is carried out.Materials and methods.  The material for the study is the works of western and Russian scholars in the field of the theory of international law, as well as the current international legal practice of implementation of the principle of equal rights and self-determination of peoples. At the same time attention has been paid to works in which the problems and theories of secession are highlighted. The methodological basis of the research includes scientific methods of cognition (dialectics, analysis and synthesis, deduction and induction, comparative legal and historical methods).Research results. As the foundations for applying the theory of the remedial secession, it is necessary to consider not only the genocide (which is the basis for the recognition of independence of Kosovo), but also the commission of large-scale war crimes, the policy of forced assimilation, the forced erasing of nation-al identity by the titular nation, whose goal is, as a rule, refusal in internal self-determination (as it was and is the case in Ukraine). The new state should be created exclusively on the basis of requirements of jus cogens norms of international law, and in some cases (Western Sahara), the rules governing the process of decolonization.Discussion and conclusions.  In this article, the author draws attention to the fact that the correlation of the principle of equal rights and self-determination of peoples and the principle of the territorial integrity of states should be considered today within the framework of the theory of the remedial secession. Secession is one of the ways of realization of the right of peoples to selfdetermination in contemporary international law. Secession from a state and the creation of an independent state must always be considered as an extreme measure and implemented only in exceptional cases.